Prediction of Energy Crisis in Indonesia Through Simulation Models System Dynamic - Gede Ryan Arya Wardana (Universitas Pendidikan Ganesha, 2022)
According to the Ministry of Energy and Mineral Resources (2016), the development of the times accompanied by an increase in the world's population, makes energy use also increase. Especially with the industrial revolution that triggers industrial growth in all sectors, making energy use also increase. The fulfillment of energy needs must be balanced with the availability of energy in an appropriate, integrated and sustainable manner in order to facilitate activities in all sectors of energy users, such as the household sector, transportation, industry, commercial, and others. The balance between energy supply and energy demand needs to be analyzed in order to give an idea of the impending energy crisis in Indonesia. The data used in this report is secondary data collected by literature study technique. The problem faced by Indonesia is that energy consumption is increasing, especially in the transportation sector, increasing to 15,000,000 terajoules in 2060, while energy production in Indonesia has increased which is not too significant. This resulted in an energy crisis. Judging from the simulation of the dynamic system approach, it is predicted that Indonesia will experience an energy crisis in 2051. In order to overcome the problem of the energy crisis in Indonesia, energy conservation is needed in various layers, both from the aspect of energy management and from the community.